OCLC PICA: a European Library Membership Organisation - Lees, Janet Mitchell (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
As always it is a great pleasure to attend a LIBER conference and be once again at the University of Graz. I am sure this past year has been a busy one for you – it certainly has for me in terms of the creation of the new OCLC PICA organisation. My purpose today is to provide you with an update on these events, to outline OCLC’s strategic priorities and OCLC PICA’s involvement in them. Before I do so I would like to say how much OCLC PICA welcomes the opportunity to become a LIBER Main Sponsor. Both OCLC Europe and Pica have been active within LIBER for many years and this new more formalised relationship has the opportunity to strengthen that link.